Leadership in the era of AI : how to grow organizational intelligence - Salisbury, Mark, 1955- (Routledge, Taylor & Francis Group, 2025)
What will be the right place for humans in the new economy of AI, avatars, automation, and 3D virtual worlds? Our job will be to bring wisdom to our workplace and the marketplace, working with intelligent machines, and this book is the roadmap. Though it addresses growing fears about the future of work, The Future of Leadership is about more than specific technologies. It's about building organizational intelligence (OI): the capability of an organization to comprehend and create knowledge relevant to its purpose. To increase organizational intelligence requires a new kind of knowledge worker--a wisdom worker--who requires a new kind of leadership. Written in an engaging business novel format, this book is the story of how to become a leader of wisdom workers and be successful in the emerging wisdom economy. Seasoned and emerging leaders in all industries, as well as talent development professionals, will value this book's insights into how to step confidently into the developing work paradigm, bringing human values and wisdom together with the latest AI in the real and virtual worlds.
Keywords: Leadership.; Artificial intelligence.; Organizational behavior.; elektronické knihy; electronic books